Red phosphorus / sulfur zinc indium composite material with high reusability as well as preparation method and application of red phosphorus / sulfur zinc indium composite material

By loading red phosphorus on sulfhydryl indium, a red phosphorus/sulfhydryl indium composite material was prepared, which solved the problem of low carrier recombination and transfer efficiency of ternary sulfide indium sulfhydryl zinc when photocatalyzed tetracycline antibiotics, and achieved It provides an efficient photocatalytic material with high efficiency degradation and good reusability.

CN119140128APending Publication Date: 2024-12-17SHANGHAI UNIVERSITY OF ELECTRIC POWER
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310715696.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-16
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

In the prior art, the ternary sulfide indium sulfide (ZnIn2S4) has low carrier recombination and transfer efficiency when photocatalyzed tetracycline antibiotics, and no reusable red phosphorus/zinc sulfide indium composite material is seen. and application inventions.

Method used

Red phosphorus/sulfuric indium composite material was prepared by loading red phosphorus on nanoflower spherical zinc sulfide indium, and dissolved in deionized water using zinc chloride, indium trichloride tetrahydrate, thioacetamide and purified red phosphorus in deionized water , magnetic stirring and heat treatment in an autoclave were carried out to obtain a red phosphorus/sulfur zinc indium composite material, and a highly efficient catalytic reaction was carried out under visible light.

Benefits of technology

The photocatalytic activity and carrier life are improved, and the tetracycline antibiotics are efficiently degraded. The catalytic performance decline of the composite material after multiple cycles is less than 6.2%, showing good reusability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119140128A_ABST
    Figure CN119140128A_ABST
Patent Text Reader

Abstract

The invention discloses a high-reusability red phosphorus / sulfur-indium-zinc composite material and a preparation method and application thereof, and belongs to the technical field of photocatalytic materials, the prepared red phosphorus / sulfur-indium-zinc (RP / ZnIn2S4) composite material has stable chemical properties, promotes separation of photo-induced electron-hole pairs, prolongs the service life of current carriers, improves the photocatalytic activity, and has good application prospects. The composite material has considerable cycle stability, the catalytic degradation performance is not obviously reduced after multiple cycles, the preparation is simple, the cost is low, high-efficiency catalytic reaction can be carried out under visible light, and the composite material is a novel green and scientific composite material with industrial application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photocatalytic degradation wastewater treatment, and specifically relates to a red phosphorus / sulfur-zinc-indium composite material with high reusability, and a preparation method and application thereof. Background Art

[0002] Since modern civilization, environmental problems caused by many new pollutants have attracted widespread attention. The abuse of antibiotics in clinical practice and their extensive use in livestock and aquaculture have threatened the environmental system. In the long run, the residual resistance genes will seriously affect human health and ecological balance. Tetracycline antibiotics are a broad-spectrum antibiotic that can quickly inhibit bacterial growth. Because of their high quality and low price, they are widely used in the treatment of human and animal diseases. Long-term use of tetracycline antibiotics causes residues in soil and water, affects the structure of biological communities, and significantly increases the ecological risk. In order to reduce the environmental risks caused by tetracycline antibiotics, researchers have proposed many research directions. Among them, photocatalytic degradation of tetracycline antibiotics shows broad application prospects in the field of environmental protection. For traditional physical treatment and biological treatment technologies, photocatalytic technology uses sunlight as a light source to degrade pollutants in the environment. It is an efficient, safe, residue-free, economical and environmentally friendly method.

[0003] Ternary sulfide zinc indium sulfide (ZnIn2S4) is used as a photocatalytic material due to its narrow band gap energy, high chemical stability, simple preparation method and significant catalytic activity in many reactions. However, the high carrier recombination and low transfer efficiency limit the photocatalytic performance of ZnIn2S4. Red phosphorus can be used as a dopant in the field of photocatalysis due to its good visible light response. By optimizing the doping ratio of red phosphorus, the effect of photocatalytic degradation of antibiotics can be improved.

[0004] At the same time, the reusability of the catalyst is also an important key point in the degradation of environmental pollutants. So far, there has been no report on the preparation and application of red phosphorus / sulfur zinc indium composite materials for photocatalytic degradation of tetracycline. Summary of the invention

[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a red phosphorus / sulfur-zinc-indium composite material with high reusability, wherein the composite material is red phosphorus loaded on nano-flower-shaped sulfur-zinc-indium, wherein the red phosphorus content is 0.5-5wt%.

[0008] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a red phosphorus / sulfur-zinc-indium composite material with high reusability.

[0009] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising:

[0010] Zinc chloride, indium trichloride tetrahydrate, thioacetamide and purified red phosphorus are dissolved in deionized water to obtain a mixed solution, which is transferred to a high-pressure reactor after magnetic stirring, heated in an oven, centrifuged and filtered after cooling to room temperature, vacuum dried and ground to obtain a red phosphorus / sulfur zinc indium composite material.

[0011] As a preferred scheme of the preparation method of the highly reusable red phosphorus / sulfur-zinc-indium composite material of the present invention, wherein: the heating treatment, wherein the heating temperature is 160-190° C., and the heating time is 20-24 hours.

[0012] As a preferred embodiment of the method for preparing the highly reusable red phosphorus / sulfur-zinc-indium composite material of the present invention, the vacuum drying is carried out at a drying temperature of 50 to 70° C. and a drying time of 10 to 12 hours.

[0013] As a preferred embodiment of the method for preparing the highly reusable red phosphorus / sulfur-zinc-indium composite material of the present invention, the concentration of zinc chloride in the mixed solution is 0.01-0.03M, the concentration of indium trichloride tetrahydrate is 0.03-0.05M, and the concentration of thioacetamide is 0.05-0.08M.

[0014] As a preferred embodiment of the method for preparing the highly reusable red phosphorus / sulfur-zinc-indium composite material of the present invention, the molar ratio of the zinc chloride, indium trichloride tetrahydrate and thioacetamide is 1:2:4.

[0015] As a preferred embodiment of the method for preparing the highly reusable red phosphorus / sulfur-zinc-indium composite material of the present invention, the red phosphorus purification method comprises:

[0016] Red phosphorus is dissolved in deionized water to obtain a red phosphorus solution with a concentration of 0.1-0.5M, which is transferred into a high-pressure reactor after magnetic stirring, heated and dried at a constant temperature, and then ultrasonicated, centrifugally filtered, vacuum dried, and ground after being cooled to room temperature to obtain purified red phosphorus.

[0017] As a preferred scheme of the preparation method of the highly reusable red phosphorus / sulfur zinc indium composite material described in the present invention, wherein: the constant temperature heating drying, wherein the heating drying temperature is 190-210°C, the heating drying time is 23-25h, and the vacuum drying, wherein the drying temperature is 50-70°C, and the drying time is 5-8h.

[0018] As a preferred solution of the method for preparing the highly reusable red phosphorus / sulfur-zinc-indium composite material of the present invention, the vacuum drying has a drying temperature of 50 to 70° C. and a drying time of 5 to 8 hours.

[0019] Another object of the present invention is to overcome the deficiencies in the prior art and provide a highly reusable red phosphorus / sulfur zinc indium composite material for use in photocatalytic degradation of tetracycline, wherein the degradation rate of the composite material for tetracycline is greater than 86.2%, and the degradation rate decreases by less than 6.2% after being reused three times.

[0020] Beneficial effects of the present invention:

[0021] (1) The present invention prepares a red phosphorus / sulfur indium zinc (RP / ZnIn2S4) composite material, which has stable chemical properties and can promote the separation of photogenerated electron-hole pairs, increase the carrier lifetime, and significantly enhance the photocatalytic activity.

[0022] (2) The present invention combines sulfur indium zinc with red phosphorus, and the two work synergistically to improve the catalytic effect of the material while having considerable cycle stability. The catalytic degradation performance after multiple cycles of catalysis is not significantly reduced.

[0023] (3) The preparation process of the present invention is simple and low-cost. The composite material prepared by a one-pot hydrothermal method can perform a high-efficiency catalytic reaction under visible light, and is a green, scientific, and new composite material with industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0025] Figure 1 This is a scanning electron microscope image of the RP (1wt.%) / ZnIn2S4 composite material obtained in Example 1 of the present invention;

[0026] Figure 2 The photocatalytic degradation results of the RP / ZnIn2S4 composite materials with different contents obtained in Examples 1 to 4 of the present invention are shown;

[0027] Figure 3 This is a diagram showing the effect of a cyclic experiment on the degradation of tetracycline by RP / ZnIn2S4 of Example 1 of the present invention and ZnIn2S4 of Comparative Example 1. DETAILED DESCRIPTION

[0028] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0029] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0030] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0031] Unless otherwise specified, the raw materials used in the present invention are commonly available in the market.

[0032] Example 1

[0033] This embodiment provides a method for synthesizing red phosphorus / sulfur indium zinc (RP / ZnIn2S4), specifically:

[0034] 1) 0.2 g of commercial red phosphorus was placed in 60 mL of deionized water, stirred with a magnetic stirrer, transferred into a 100 mL high-pressure reactor, kept constant temperature in an oven at 200° C. for 24 hours, cooled to room temperature, ultrasonicated for 2 hours, centrifuged and filtered, dried in a vacuum oven at 60° C. for 6 hours, and ground to obtain purified red phosphorus (RP).

[0035] 2) 1mmol zinc chloride (ZnCl2), 2mmol indium trichloride tetrahydrate (InCl3·4H2O), and 4mmol thioacetamide (TAA) are dissolved in 60mL deionized water, and then 1wt.% purified red phosphorus is added. After stirring for 30min under a magnetic stirrer, the mixture is placed in a 100mL high-pressure reactor and heated in an oven at 180°C for 24 hours. After cooling to room temperature, the mixture is repeatedly centrifuged and filtered with deionized water and anhydrous ethanol, and treated in a vacuum drying oven at 60°C for 12 hours. The mixture is ground to obtain a red phosphorus / indium zinc sulfide (RP / ZnIn2S4) composite material.

[0036] The obtained product is Figure 1 As shown in the scanning electron microscope image, it can be observed that a portion of red phosphorus is loaded on the nanoflower-shaped ZnIn2S4. The SEM results fully confirm the successful preparation of RP / ZnIn2S4.

[0037] Example 2

[0038] The difference between this embodiment and embodiment 1 is that the content of red phosphorus is adjusted to 3 wt.%, and the rest of the preparation process is the same as that of embodiment 1 to obtain the (RP / ZnIn2S4) composite material of this embodiment.

[0039] Example 3

[0040] The difference between this embodiment and embodiment 1 is that the content of red phosphorus is adjusted to 0.5wt.%, and the rest of the preparation process is the same as that of embodiment 1 to obtain the (RP / ZnIn2S4) composite material of this embodiment.

[0041] Example 4

[0042] The difference between this embodiment and embodiment 1 is that the content of red phosphorus is adjusted to 5 wt.%, and the rest of the preparation process is the same as that of embodiment 1 to obtain the (RP / ZnIn2S4) composite material of this embodiment.

[0043] Comparative Example 1

[0044] 1mmol zinc chloride (ZnCl2), 2mmol indium trichloride tetrahydrate (InCl3·4H2O), and 4mmol thioacetamide (TAA) were dissolved in 60mL deionized water, stirred for 30min under a magnetic stirrer, placed in a 100mL high-pressure reactor, and heated in an oven at 180°C for 24 hours. After cooling to room temperature, the mixture was repeatedly centrifuged and filtered with deionized water and anhydrous ethanol, treated in a vacuum drying oven at 60°C for 12 hours, and ground to obtain zinc indium sulfide (ZnIn2S4).

[0045] Comparative Example 2

[0046] 0.2 g of commercial red phosphorus was placed in 60 mL of deionized water, stirred with a magnetic stirrer, transferred into a 100 mL autoclave, kept constant temperature in an oven at 200 ° C for 24 hours, brought to room temperature, ultrasonicated for 2 hours, and then centrifuged and filtered. After drying in a vacuum oven at 60 ° C for 6 hours, the purified red phosphorus (RP) was obtained by grinding.

[0047] Photocatalytic performance test of red phosphorus / indium zinc sulfide (RP / ZnIn2S4) composite material:

[0048] 30 mg of the material prepared in each example and comparative example was placed in 100 mL of 30 mg / L tetracycline (TC) solution, and a dark reaction was first performed to achieve adsorption-desorption equilibrium;

[0049] Then, a 300W xenon lamp equipped with an optical cutoff filter was turned on, and the solution was exposed to the light for a photodegradation experiment. 4 mL of the solution was collected as a sample at 10-minute intervals, and the supernatant was obtained to measure the absorbance of tetracycline on a Shimadzu UV-2550 ultraviolet-visible spectrophotometer.

[0050] C / C0 was used to evaluate the degradation rate, where C was the concentration of tetracycline in the sample after t hours of illumination, and C0 was the initial tetracycline concentration of the sample.

[0051] The results are as follows Figure 2 As shown, it is a photocatalytic degradation diagram of tetracycline in the presence of different contents of RP / ZnIn2S4 composite materials. The adsorption-desorption equilibrium is reached after 30 minutes of dark reaction. It can be seen from the figure that with the increase of red phosphorus content, the photocatalytic performance of the RP / ZnIn2S4) composite material gradually increases and then decreases. Among them, the degradation rate of the RP (1wt.%) / ZnIn2S4) composite material after 60 minutes of catalytic reaction under light conditions is 86.2%, showing the best photocatalytic effect.

[0052] Figure 3 It is a cycle experiment effect diagram of tetracycline degradation by RP / ZnIn2S4 of Example 1 of the present invention and ZnIn2S4 of Comparative Example 1. It can be seen that after three cycle experiments, the degradation rate of the RP / ZnIn2S4 composite material decreased by 6.1%, while the decrease of ZnIn2S4 was 7.6%. At the same time, the degradation rate of the purified red phosphorus material after one cycle was significantly greater than that of the RP / ZnIn2S4 composite material, so the inventor did not conduct further stability tests. This shows that the photocatalytic stability and reusability of the material can be greatly improved by compounding red phosphorus and sulfur indium zinc.

[0053] In summary, the present invention discloses a highly reusable red phosphorus / sulfur zinc indium composite material and its preparation method and application, which belongs to the technical field of photocatalytic materials. The prepared red phosphorus / sulfur zinc indium (RP / ZnIn2S4) composite material has stable chemical properties, promotes the separation of photogenerated electron-hole pairs, increases the lifespan of carriers, and improves photocatalytic activity. The present invention has considerable cycle stability, and the catalytic degradation performance is not significantly reduced after multiple cycles. The present invention is simple to prepare, low in cost, and can carry out efficient catalytic reactions under visible light. It is a green and scientific new composite material with industrial application prospects.

[0054] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A highly reusable red phosphorus / sulfur-zinc-indium composite material, characterized in that: The composite material is red phosphorus loaded on sulfur-zinc-indium nano-flower-shaped balls, wherein the content of red phosphorus is 0.5-5wt%.

2. The method for preparing the red phosphorus / sulfur-zinc-indium composite material with high reusability as claimed in claim 1, characterized in that: include, Zinc chloride, indium trichloride tetrahydrate, thioacetamide and purified red phosphorus are dissolved in deionized water to obtain a mixed solution, which is transferred to a high-pressure reactor after magnetic stirring, heated in an oven, centrifuged and filtered after cooling to room temperature, vacuum dried and ground to obtain a red phosphorus / sulfur zinc indium composite material.

3. The method for preparing the red phosphorus / sulfur-zinc-indium composite material with high reusability as claimed in claim 2, characterized in that: The heating treatment comprises a heating temperature of 160 to 190° C. and a heating time of 20 to 24 hours.

4. The method for preparing the red phosphorus / sulfur-zinc-indium composite material with high reusability as claimed in claim 2, characterized in that: The vacuum drying has a drying temperature of 50 to 70° C. and a drying time of 10 to 12 hours.

5. The method for preparing the red phosphorus / sulfur-zinc-indium composite material with high reusability as claimed in claim 2, characterized in that: The concentration of zinc chloride in the mixed solution is 0.01-0.03M, the concentration of indium chloride tetrahydrate is 0.03-0.05M, and the concentration of thioacetamide is 0.05-0.08M.

6. The method for preparing the red phosphorus / sulfur-zinc-indium composite material with high reusability as claimed in claim 4, characterized in that: The molar ratio of the zinc chloride, indium trichloride tetrahydrate and thioacetamide is 1:2:

4.

7. The method for preparing the red phosphorus / sulfur-zinc-indium composite material with high reusability as claimed in claim 2, characterized in that: The red phosphorus purification method comprises: Red phosphorus is dissolved in deionized water to obtain a red phosphorus solution with a concentration of 0.1-0.5M, which is transferred into a high-pressure reactor after magnetic stirring, heated and dried at a constant temperature, and then ultrasonicated, centrifugally filtered, vacuum dried, and ground after being cooled to room temperature to obtain purified red phosphorus.

8. The method for preparing the red phosphorus / sulfur-zinc-indium composite material with high reusability as claimed in claim 6, characterized in that: The constant temperature heating drying, wherein the heating drying temperature is 190-210° C., and the heating drying time is 23-25 ​​hours; the vacuum drying, wherein the drying temperature is 50-70° C., and the drying time is 5-8 hours.

9. Use of the red phosphorus / sulfur-zinc-indium composite material as claimed in claim 1 in photocatalytic degradation of tetracycline.

10. Use of the red phosphorus / sulfur-zinc-indium composite material according to claim 9 in photocatalytic degradation of tetracycline, characterized in that: The degradation rate of tetracycline by the composite material is greater than 86.2%, and the degradation rate decreases by less than 6.2% after being reused three times.